Light and Death : Figuration in Spenser, Kepler, Donne, Milton - Anderson, Judith H. (Book collections on Project MUSE., 2017)
"Death, light, figuration and, especially, analogical expressions of figuration, are the primary subjects of this book. They generate associated interests: the relation of literature and science, the methodology of thought and argument, and the processes of narrative, discovery, and interpretation. Creativity, optics, rhetoric, and language are focal as well"--